Semantic versus thematic clustering of new lexical items : a textbook analysis - Kujala, Jaakko (2015)
Vocabulary acquisition is an essential part of learning a second language, yet textbook designers and language educators often have difficulties with creat-ing such vocabulary acquisition exercises and materials that would best en-hance the development of this crucial skill. There is indeed a growing body of evidence suggesting that semantic clustering of new lexical items impedes L2 vocabulary acquisition, but still semantic clustering is the prevalent meth-od used in contemporary EFL textbooks. This study focused on one EFL book series in particular, which can justifiably be seen as a representative of all contemporary beginner-level EFL textbooks in Finnish elementary schools. The contents of the book were analyzed in the light of current research on vocabulary acquisition, and an alternative organizing method of new lexical items, thematic clustering, was reviewed.